Transporte quântico decoerente em sistemas mesoscópicos - Oliveira, Elenilda Josefa de (2015)
The scientific advances we have experienced in recent decades have enabled us to produce systems in the mesoscopic scale. These systems have become very useful as research tools in various areas of science. In mesoscopic physics the ondulatory characteristic of electrons is more evident than in classical physics and the electron conduction process is better represented by the wave function that describes it. Examples of application of mesoscopic systems are quantum dots which are open cavities where electrons are limited to flow through. Thus, the objective of this work is to study the effects of decoherence in the transport of electrons in two systems: i) quantum dot with a fictitious guide and ii) quantum dot with stub, where we take into account ondulatory properties of electrons. The formalism that we use is the scattering matrix, which relates the incoming and outgoing amplitudes in the scattering of waves coming in and out of the scattering region. Since the studied systems are chaotic, the scattering matrices can be treated as random. These matrices were generated by computational simulation and then the conductance values were computed. The conductance distribution was obtained by means of probabilistic analysis.